2003
DOI: 10.1046/j.1365-2125.2003.01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of CYP2C9 and CYP2C19 in the Beninese and Belgian populations

Abstract: Aims  To investigate the distribution of cytochrome P450 2C9 (CYP2C9) and 2C19 (CYP2C19) genotype frequencies in the Beninese and Belgian Caucasian populations. Methods  Beninese (n = 111) and Belgian (n = 121) were genotyped for CYP2C9*2, *3, *4, *5, and *11 as well as for CYP2C19*2 and*3. Results  The distribution of alleles was: CYP2C9*1: 95.5 vs. 82.2% (P < 0.001); CYP2C9*2: 0 vs. 10% (P < 0.001); CYP2C9*3: 0 vs. 7.4% (P < 0.01); CYP2C9*4: both 0%; CYP2C9*5: 1.8 vs. 0% (P = 0.05); and CYP2C9*11: 2.7 vs. 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
52
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 20 publications
13
52
4
Order By: Relevance
“…It has been shown that a higher [49] These are some of the representative population studies from various geographical areas. Differences in the allele frequencies were measured by Fisher exact test NS indicates that there were no significant differences (p [ 0.05) Genetic polymorphism of CYP2C19 911 [60] concentration of omeprazole in PMs results in great gastric acid suppression as compared with EMs [26].…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that a higher [49] These are some of the representative population studies from various geographical areas. Differences in the allele frequencies were measured by Fisher exact test NS indicates that there were no significant differences (p [ 0.05) Genetic polymorphism of CYP2C19 911 [60] concentration of omeprazole in PMs results in great gastric acid suppression as compared with EMs [26].…”
Section: Discussionmentioning
confidence: 98%
“…Population diversity CYP2C9*2 and *3 allele frequencies were compared among the sampled populations and also among data previously published for 12 European populations scattered all over the continent from the United Kingdom, 17 Holland, 18 France, 16 Germany, 19 Hungary, 20 Italy, 21 Sweden, 22 Turkey, 12 Belgium, 13 Iran, 14 Spain 11 and the Europeans from the United States of America 23 (Table 4). No significant differences were observed among our five samples in any of the CYP2C9 variants.…”
Section: Validation Studymentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23] Here we present a descriptive study of the prevalence of the most relevant CYP2C9 polymorphisms, CYP2C9*1 (wild type), CYP2C9*2 and CYP2C9*3, in population samples from both Spain (Basque Country, Catalonia, Central Spain and Galicia) and northern Italy (Verona) summing up a total of 1240 individuals. We also compared the allele frequencies on our population samples with those previously published for other European populations.…”
Section: Introductionmentioning
confidence: 99%
“…Even though our study is limited to the most important CYP alleles (SNPs) and a relatively small sample, it clearly the following frequencies: France 8.0 %, Belgium 7.4 %, Hungary 8.8 %, Croatia 9.5 %, Greece 8.1 %, and Macedonia 7.3 % (14,15,23,(26)(27)(28)..…”
Section: Resultsmentioning
confidence: 99%